Implementation of Library Policy in Kuningan Regency: A Case Study of Pelita Hati Library in Nanggerang Jaya Village - Dedeh Ermawati; Siti Khumayah (Syntax Literate, 2026)
Village libraries play a vital role in improving public literacy, as mandated by Law Number 43 of 2007 concerning Libraries. However, many village libraries remain poorly managed, including Pelita Hati Library in Nanggerang Jaya Village, Kuningan Regency. This research aims to examine how the village government implements policies related to the Pelita Hati library, identify supporting and inhibiting factors, and find out the efforts made to support the sustainability of the village library operation. This study used a qualitative method with a descriptive approach. Data collection is carried out through interviews, direct observations, and documentation from parties involved in the implementation of the library. The researcher also analyzed the data using the theory of policy implementation put forward by George C. Edwards III. This theory involves several aspects such as communication, resources, disposition, and bureaucratic structure. The results of the research show that the implementation of policies related to library administration has been implemented, but it has not been effective. The village government has been quite active in communicating and committing, but there are still obstacles due to limited resources, facilities and infrastructure. On the other hand, the village government has made several efforts, such as socialization to residents, cooperation in literacy activities, and continues to allocate resources and support the management of the library in stages. This study concludes that to maintain the sustainability of village libraries, there is a need for policy support, increased resources, and active involvement from the community.